Numerical simulation of combined transient natural convection and volumetric radiation inside hollow bricks - Mohammad Omidpanah; Seyed Ali Agha Mirjalily; Hadi Kargarsharifabad; Shahin Shoeibi (Journal of Heat and Mass Transfer Research, 2021)
This study simulated the flow and temperature field inside hollow bricks using well-known geometries to investigate the transient thermal behavior in both solid and fluid regions. To this end, a set of governing equations was solved simultaneously for an absorbing-emitting, isotropically scattering gas and solid region. To discretize the equations, the finite volume method was applied and the radiative transfer equation was calculated using the discrete ordinate method. Furthermore, the block off method is used to distinguish between solid and fluid media in the computational domain. The obtained results show that the rate of heat transfer is minimized in geometries having vertical rectangle sub cavities and their wall emissivity tends to zero. Moreover, the time required to reach steady state condition is an increasing function of total heat flux.